Model Knowledge Management Di Perguruan Tinggi - Dyah Budiastuti (Bina Nusantara University, 2012)
Business conditions change quickly, pushing companies to change the way they compete. The Era of knowledge-based economy provides challenges for collaboration, innovation, adaptation, technological mastery and market, as well as intellectual assets management company. Relying on existing core competencies does not guarantee the company able to create competitive advantages. To face the challenges of existing companies must be able to manage the knowledge that having through the application of Knowledge Management (KM).Similarly with colleges based on human capital, the need to manage organizations that encourage the formation of cultural knowledge creation, knowledge sharing, and knowledge utilization through the application of Knowledge Management. With Knowledge Management, recognition quality of a lecturer is not based only on seniority but on the extent to which lecturers are acts as a general user, specialist, solution communities, as well as professional.